Управління конкурентоспроможністю підприємства - Геращенко, Ірина Олексіївна; Шмадченко, О. О. (Український державний університет залізничного транспорту, 2015)
В статті систематизовано поняття конкурентоспроможності підприємства, розглянуто багатогранність трактувань вчених економістів, наведено систему показників для оцінки становища конкурентоспроможності підприємства, розглянуто основні рівні конкурентоспроможності підприємства, охарактеризовано методи оцінки конкурентоспроможності та розроблено модель для оцінки становища підприємства і прийняття відповідного рішення в управлінні конкурентоспроможністю підприємства.

In the paper the concept of enterprise competitiveness, scientists examined the diversity of interpretations of economists, the definition from our point of view, the notion of competitiveness, considered a system of indicators to assess the situation of the competitiveness of enterprises, the basic level of competitiveness of enterprises describing the behavior of enterprises in each of the levels characteristic of methods for assessing competitiveness. The model of competitiveness management company, determined the factors which influence the company projected level of enterprise competitiveness by changing the actions of these factors, the ways are systematized and it means to increase the competitiveness of developing a set of measures to improve the competitiveness and further appropriate action in enterprise management.
Management competitiveness of enterprise
Keywords: управління; конкуренція; конкурентоспроможність підприємства; конкурент; management; competition; competitiveness; competitor